2018
DOI: 10.1016/j.cstp.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Appraising the market for bicycle sharing schemes: Perceived service quality, satisfaction, and behavioural intention in London

Abstract: The implementation of bicycle sharing schemes represents an important innovation in urban public transport since the turn of the millennium. These schemes have spread rapidly and are now present in cities with varying economic, environmental, and structural conditions. Developing strategies through which to attract new members to join the scheme and retain existing members is a fundamental requirement for scheme success. The research reported in this paper provides guidance on this issue through a case study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…The scheme, after incremental strategic expansions, now spreads across 100 km 2 of London and is the largest cycle hire scheme in Europe, with 11,500 bicycles available across 750 docking stations [65]. It has approximately 240,000 active members making over 10 million annual bicycle hires, and its continued expansion is viewed as a central component of the Mayor's policy to transform London's transport system into one which is based on sustainable modes [66]. Therefore, the scheme is subsidised and promoted heavily by Transport for London and is well-linked with all the public transport modes of the city.…”
Section: Stories Of Successmentioning
confidence: 99%
“…The scheme, after incremental strategic expansions, now spreads across 100 km 2 of London and is the largest cycle hire scheme in Europe, with 11,500 bicycles available across 750 docking stations [65]. It has approximately 240,000 active members making over 10 million annual bicycle hires, and its continued expansion is viewed as a central component of the Mayor's policy to transform London's transport system into one which is based on sustainable modes [66]. Therefore, the scheme is subsidised and promoted heavily by Transport for London and is well-linked with all the public transport modes of the city.…”
Section: Stories Of Successmentioning
confidence: 99%
“…In recent years increasing bicycle use is considered as a solution for traffic issues. Commuting by bicycle can help to make the transport system more sustainable because demands little energy and other resources, and has a range of health, accessibility, environmental and socioeconomic advantages (Midgley, 2011;Bernatchez et al, 2015;Karki and Tao, 2016;Morton, 2018). Providing rental bicycles and bicycle sharing systems (BSSs) is one of the policies of governments for removing the obstacles of cycling in cities and encourage people to ride bicycles.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing number of private vehicles across the globe has caused great social and environmental problems such as noise, traffic congestion, and air pollution [1]. In response to this, bike-sharing systems have been adopted to reduce the use of private cars in short-distance trips [2,3,4,5]. Previous studies have shown that bike sharing is flexible, economical, and good for health; it helps cut down emissions, ease congestion, and reduce fuel usage; and it also supports multimodal transport connections [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%